2023
DOI: 10.5423/ppj.oa.02.2023.0035
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Green and Chemically Synthesized ZnO Nanoparticles against Alternaria citri, the Causal Agent Citrus Black Rot

Abstract: Citrus black rot is a serious disease of citrus plants caused by <i>Alternaria citri</i>. The current study aimed to synthesize zinc oxide nanoparticles (ZnO-NPs) by chemically or green method and investigate their antifungal activity against <i>A. citri</i>. The sizes of synthesized as measured by transmission electron microscope of ZnO-NPs were 88 and 65 nm for chemical and green methods, respectively. The studied prepared ZnO-NPs were applied, <i>in vitro</i> and <i>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Dangana et al prepared ZnO nanoparticles using extracts obtained from the leaves of Chaya Cnidoscolus aconitifolius and used them as nano fertilizers on Sorghum bicolour plants [9]. Elshafie et al carried out the green synthesis of ZnO nanoparticles using Moringa oleifera leaves [10]. Rini et al reported a green method of synthesizing ZnO nanoparticles using pineapple-peel extract and evaluated their antibacterial activity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Dangana et al prepared ZnO nanoparticles using extracts obtained from the leaves of Chaya Cnidoscolus aconitifolius and used them as nano fertilizers on Sorghum bicolour plants [9]. Elshafie et al carried out the green synthesis of ZnO nanoparticles using Moringa oleifera leaves [10]. Rini et al reported a green method of synthesizing ZnO nanoparticles using pineapple-peel extract and evaluated their antibacterial activity [11].…”
Section: Introductionmentioning
confidence: 99%
“…The stock solution was stored in the refrigerator at 4 °C. This solution was also used for the investigation of neem phytochemistry ( Elumalai et al, 2012 ; El-Saber, 2021 ; Elshafie et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…The particles obtained were subjected to centrifugation, and the resulting solid masses were gathered. The pellet was dried and calcined at 300 °C for 2 h. The process was followed to obtain white colored nanoparticles ( Pal et al, 2018 ; Zambri et al, 2019 ; El-Saber, 2021 ; Elshafie et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…20 ZnO NPs have found several uses in various fields, including catalysis, antioxidant activity, environmental protection, electronics, cosmetics, communication, biology, and pharmaceutical industries. 21–23 Furthermore, due to their antimicrobial, 24 antifungal, 25 anti-diabetic, 26 and insecticidal 27 features, ZnO NPs have a vast variety of medical utilities that include bio-sensing, 28 drug transport, 29 and nanomedicines. 30 The use of different parts of plant extracts is a promising technique for the synthesis of ZnO NPs.…”
Section: Introductionmentioning
confidence: 99%